Analisis Efisiensi Saluran Pemasaran dan Distribusi Margin Keuntungan Jeruk Manis (Citrus x sinensis) di Kecamatan Meureubo, Kabupaten Aceh Barat - Katoha, Rahmad; Fitri, Sri; Khumaira, Khumaira (Jurnal Agrisep, 2025)
Sweet oranges is a horticultural commodities that is prioritized for development, because orange farming provides high profits, so it can be used as a source of income for farmers. The aim of this research is to determine the marketing channels and margins for sweet oranges (Citrus x Sinesis) in Meureubo District, West Aceh Regency. The research method used is a quantitative method and a sampling technique using saturated samples. The analysis model used is marketing channel analysis and marketing margin analysis. The results of the research show that the marketing channels for Sweet Oranges (Citrus x Sinesis) in Meureubo District, West Aceh Regency, have 3 channel patterns consisting of marketing channel pattern I, namely Farmers-Consumers, marketing channel II, namely Farmers-Retailers-Consumers and marketing channel III, namely Farmers-Collectors-Retailers-Consumers. Marketing profit margin in marketing channel I is Rp. 20,570.00/Kg (97.95%). Profit margin in the second marketing channel, retailers obtain a profit margin of Rp. 1,320.00/Kg (6.29%). Then the profit margin on the third marketing channel of the collecting traders gets a profit margin of Rp. 1,150.00/Kg (5.48%) and retailers Rp. 1,420.00/Kg (6.76%). The efficiency of marketing channel I has an efficiency level of 2.05%, marketing channel II has an efficiency level of 3.58% and marketing channel III has an efficiency level of 8.41%. This shows that the most efficient channel is marketing channel I because marketing costs in channel I are smaller and there is only one marketing institution involved in this marketing channel.